Life After Carbon - Plastrik, Peter (Island Press/Center for Resource Economics, 2018)
"Enlightening." Seattle Book Review "Life After Carbon is a highly engaging, forward-looking study of how modern cities are innovating to survive...This superbbook looks at the evolution of the world's cities and their challenging future...Life After Carbon is essential reading for anyone with a stake in the development of tomorrow's cities." Foreword "Life After Carbon is a vivid and multifaceted look at the cities leading the global transition to a post-carbon world. Drawing insight from and connections among the communities at the forefront of urban climate innovation, Plastrik and Cleveland chart much-needed and promising pathways into the future." Edward Mazria, Architecture 2030 "In Life After Carbon, Plastrik and Cleveland lay out a hidden upside of climate action, detailing how innovative cities leading the fight against climate change are developing a new model for urban development that promises better cities in a carbon-free economy. This is an important and inspiring book for business leaders and other professionals in their efforts to create more livable cities while strengthening climate resilience." Mindy Lubber, CEO of Ceres "Plastrik and Cleveland give readers nothing less than a new and compelling vision for what cities could be: carbon-free, climate adaptive, biophilic and nature-rich, with restorative closed-loop metabolisms, and, of course, wonderful places in which to live. Together these stories, ideas, and emerging practices chart an optimistic urban future. Life After Carbon is an essential resource for planners, mayors, and citizens (all of us) with a vested interest in accelerating this future."Timothy Beatley, Teresa Heinz Professor of Sustainable Communities at the School of Architecture at the University of Virginia "Plastrik and Cleveland have written a timely, affirmative account of urban innovation and transformation in the face of climate change. Their vision of the post-carbon city is captivating and compelling, with ideas that are tangible, transferable, and scalable. This is a much-needed contribution at a pivotal moment." Bruce Katz, coauthor, "The New Localism: How Cities Can Thrive in the Age of Populism".